2000
DOI: 10.1038/sj.onc.1204082
|View full text |Cite
|
Sign up to set email alerts
|

The EGF receptor family as targets for cancer therapy

Abstract: Human carcinomas frequently express high levels of receptors in the EGF receptor family, and overexpression of at least two of these receptors, the EGF receptor (EGFr) and closely related ErbB2, has been associated with a more aggressive clinical behavior. Further, transfection or activation of high levels of these two receptors in nonmalignant cell lines can lead to a transformed phenotype. For these reasons therapies directed at preventing the function of these receptors have the potential to be useful anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
864
1
19

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,231 publications
(896 citation statements)
references
References 100 publications
6
864
1
19
Order By: Relevance
“…5 Cetuximab (Erbitux; Merck KgaA, Darmstadt, Germany) is an immunoglobulin G1 monoclonal antibody that specifically targets EGFR, competitively inhibiting ligand binding and ligand-dependent downstream signaling. 6 Phase 1 clinical trials demonstrated the safety of cetuximab combined with CP 7 and cetuximab combined with radiation therapy 8 in SCCs other than anal carcinoma. Also, in phase 3 clinical trials, adding cetuximab to first-line chemotherapy or RT improves outcomes in various types of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…5 Cetuximab (Erbitux; Merck KgaA, Darmstadt, Germany) is an immunoglobulin G1 monoclonal antibody that specifically targets EGFR, competitively inhibiting ligand binding and ligand-dependent downstream signaling. 6 Phase 1 clinical trials demonstrated the safety of cetuximab combined with CP 7 and cetuximab combined with radiation therapy 8 in SCCs other than anal carcinoma. Also, in phase 3 clinical trials, adding cetuximab to first-line chemotherapy or RT improves outcomes in various types of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…ErbB1 and ErbB2 are well-established oncogenes and cancer drug targets. They are implicated in the pathogenesis of various epithelial and neural malignancies, and their overactivity is associated with poor patient outcome (Slamon et al, 1987;Mendelsohn and Baselga, 2000;Hynes and Lane, 2005). Targeted therapeutics including both monoclonal antibodies and small-molecular-weight kinase inhibitors blocking the functions of ErbB1 and/or ErbB2 have demonstrated therapeutic effect in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor (EGF) and its family members (e.g., transforming growth factor-a) affect cell growth, differentiation, motility, adhesion and tumorigenesis by interaction with the EGF receptor (EGFR), a transmembrane tyrosine kinase growth factor receptor (Boonstra et al, 1995;Mendelsohn and Baselga, 2000;Holbro et al, 2003;Mendelsohn and Baselga, 2003;Shilo, 2003). EGFR, also known as ErbB-1, is the prototype of the ErbB family, which also includes ErbB-2 (c-neu, HER2), ErbB-3 and ErbB-4 (Lin et al, 1984;Bargmann et al, 1986;Kraus et al, 1989;Plowman et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…By heterodimerizing with ErbB members, ErbB-2 augments EGF/EGF-like ligand signaling (Karunagaran et al, 1996;Graus-Porta et al, 1997). EGFR promotes pubertal breast ductal morphogenesis in mice, and both EGFR and ErbB-2 are relevant in pathogenesis and behavior of breast and other human cancers (Berger et al, 1988;Xie et al, 1997;Biscardi et al, 2000;Mendelsohn and Baselga, 2000;Stern, 2000;Mendelsohn and Baselga, 2003). Increased expression and signaling of EGFR and/or ErbB-2 is associated with more aggressive clinical behavior and correlates with a poor prognosis (Alroy and Yarden, 1997).…”
Section: Introductionmentioning
confidence: 99%